IMPLEMENTASI SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) DENGAN METODE HIRADC DI PT. INTI GANDA PERDANA (STUDI KASUS DEPARTEMEN PRODUKSI) - Ardyanto, Slamet; Indriastiningsih, Erna; Nugrahadi, Bekti (ITB AAS Indonesia Surakarta, 2025)
Occupational Health and Safety (OHS) is a crucial aspect of manufacturing industry operations, particularly in activities involving interactions between humans, machines, and materials. This study aims to identify, evaluate, and classify potential hazards and the associated risk levels in various work processes, including Picking Differential Carrier, Small Part Preparation, Brake Assembly & Retainer Press, Axle Shaft & Brake Install, and Nut Brake Tightening. The analysis method employs a systematic approach to different types of hazards—chemical, physical, mechanical, and ergonomic—followed by an assessment of probability and impact levels. The results indicate that most hazards fall within the